Comparison of the SenSmart™ and the INVOS™ neonatal cerebral near-infrared spectrometry devices - Wirayannawat, Wariphan; Amawat, Jutharat; Yamsiri, Nattaya; Paes, Bosco; Kitsommart, Ratchada (Frontiers in Pediatrics, 2023)
Objectives: To determine the correlation and agreement between the SenSmart™ and the INVOS™ devices of neonatal cerebral regional oxygen saturation (CrSO2) measurements using neonatal sensors. The secondary objective was to develop a regression model that predicts CrSO2-INVOS values using CrSO2-SenSmart indices and determine whether the values between the devices are interchangeable.Methods: A prospective, cross-sectional study was conducted in infants during the first 4 weeks of life. Simultaneous, bilateral CrSO2 was measured using the SenSmart™X100 (CrSo2-SenSmart) or INVOS™ 5100C (CrSO2-INVOS) device in each frontoparietal area for 2 hours.Five-minute CrSO2 values were extracted for analysis.Results: Thirty infants were recruited with 720 pairwise measurements and 26 (84%) were evaluated in the first week of life. Mean gestational age of the preterm and term infants was (30.9±2.8 [n=14] and 38.8±1.1 [n=16]) weeks, respectively. Overall CrSO2-was 77.08 ± 9.70% and 71.45 ± 12.74% for the SenSmart and INVOS, respectively (p <0.001). The correlation coefficient (r) between the CrSO2-SenSmart and INVOS was 0.20 (p <0.001). The mean difference between the CrSO2-SenSmart and INVOS was 5.63±13.87% with -21.6% to 32.8% limits of agreement. The r and mean difference was 0.39 (p <0.001) and 8.87±12.58% in preterm infants, and 0.06 (p =0.27) and 2.79±14.34 in term infants.The CrSO2-SenSmart tended to read higher than the CrSO2-INVOS device. There was no correlation between the CrSO2-SenSmart and the CrSO2-INVOS in term infants and it was weak in preterms. Due to imprecise agreement, the CrSO2-SenSmart values are not interchangeable with those of the CrSO2-INVOS.